The impact of internationalization on Japanese higher education : is Japanese education really changing? - Mock, John, 1949-; Kawamura, Hiroaki; Naganuma, Naeko (Global perspectives on higher education ;, 2016)
Deftly avoiding both the zealous idealism of the policymaker and the cynical realism of the practitioner, the contributions to this volume offer empirically grounded, culturally nuanced analyses of university internationalisation in practice. Recommended reading for anyone interested in Japanese higher education today, and a fine example of how to blend engaging 'insider' stories with rigorous scholarly analysis.